Reducing the Nicotine Content of Cigarettes: Effects in Smokers With Mental Health Conditions and Socioeconomic Disadvantages. (23rd December 2019) - Tidey, Jennifer W; Muscat, Joshua E; Foulds, Jonathan; Evins, A Eden; Gaalema, Diann E; Denlinger-Apte, Rachel L
Abstract: In this commentary, we review results from laboratory studies and randomized clinical trials that have examined the effects of very low–nicotine-content cigarette use in smokers with mental health conditions and socioeconomic disadvantages. On the basis of scientific evidence to date, we conclude that a reduced-nicotine standard for cigarettes would likely reduce cigarette smoking in these populations, without increasing psychiatric symptoms or compensatory smoking.